2003
DOI: 10.1080/09593330309385548
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Cu and Zn from swine raising wastewater using organic filters

Abstract: Rice husks, coffee bean skins, sugar cane bagasse, maize cobs, saw dust and fine charcoal dust were evaluated as filters for the removal of heavy metals (Cu and Zn) from the waste water of swine raising installations. The specific mass, pH and the sum of bases and removable acids were determined to characterize each of the filter materials. Each filtering material was placed in a 100 mm diameter, 600 mm long, PVC column to a height of 500 mm under 12,500 N m(-2) of compression. Chemical and physical analyses w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 5 publications
0
7
0
5
Order By: Relevance
“…Other studies showed the capacity of the metal ions to bind onto organic sorbents (sawdust, rice husk, etc.) was 96% for Cd 2+ , 98% for Pb 2+ and 43.6% for Cu 2+ [7,8].…”
Section: Heat Treatmentmentioning
confidence: 98%
See 2 more Smart Citations
“…Other studies showed the capacity of the metal ions to bind onto organic sorbents (sawdust, rice husk, etc.) was 96% for Cd 2+ , 98% for Pb 2+ and 43.6% for Cu 2+ [7,8].…”
Section: Heat Treatmentmentioning
confidence: 98%
“…de Matos et al [8] used columns of organic filter for removal of Cu(II) and Zn(II) from waste water. Each filtering material was placed in a 100 mm diameter, 600 mm long, PVC column to a height of 500 mm under 12500 N m −2 of compression.…”
Section: Column Experiments By Wastewatermentioning
confidence: 99%
See 1 more Smart Citation
“…These results have shown that sugarcane is a crop that is able to grow in areas contaminated with metals (SeguraMunoz et al 2006). Extra findings revealed that the cane residue or bagasse can also be used to remove Cu and Zn from the wastewater of electroplating industries (Sousa et al 2009) and swine raising installations (De Matos et al 2003).…”
Section: Toxic Metal Stressmentioning
confidence: 99%
“…Typically, these materials are considered as agro-industrial residues, representing an environmental problem (Albertini et al, 2007). Sugarcane bagasse has been used as adsorbent material for the recovery of wastewater contaminated with heavy metals, such as in cadmium, nickel, copper and zinc adsorption in wastewater from agribusiness and mining and metallurgical industries (De Matos et al, 2003;Grupta et al, 2003;Grupta & Ali, 2004). This material is an agricultural residue obtained in large quantities in Brazil, consisting of four fractions, namely: 45% fiber, 2-3% insoluble solids, 2-3% soluble solids and 50% water.…”
Section: Introductionmentioning
confidence: 99%